The EU Nitrates Directive: A European Approach to Combat Water Pollution from Agriculture - Gert J. Monteny (The Scientific World Journal)
From 1991 onward, the European Union (EU) member states have had to comply with the Nitrates Directive. The aim of this directive is to sustainably protect ground and surface waters from pollution with nitrogen (nitrate) originating from agriculture. Agriculture is, on an EU level, the largest single source of nitrate (runoff, leaching) pollution, although households and industries also contribute to some extent. An important element in the directive is the reporting every 4 years on the monitoring of ground- and surface-water quality. Furthermore, all 15 member states are compelled to designate so-called Nitrate Vulnerable Zones (NVZs). These are regions where the nitrate concentrations in the groundwater amount to 50 mg/l or more. In addition to Codes of Good Agricultural Practice, valid on a countrywide basis and often consisting of voluntary-based measures, specific Action Programmes with mandatory measures have to be developed for the NVZs. The first reporting period ended in 1995. This paper describes the progress in member states’ compliance with the Nitrates Directive during the second period (1996–1999), with a focus on the agricultural practices and action pro- grammes. An evaluation of the member states’ reports shows that good progress is being made on the farmers’ awareness of the need to comply with EU regulations on the protection of the aquatic environment. Action programmes are valuable tools to enforce measures that lead to a reduction of the water pollution by agricultural activities. Regional projects show that significant improvements can be achieved (e.g., reduced fertiliser inputs) while maintaining crop yields and thus maintaining the economic potential of agriculture.